2023
DOI: 10.3390/molecules28062554
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Extraction of Protein from Moringa oleifera Seeds and Its Impact on Techno-Functional Properties

Abstract: Plant proteins can be an important alternative to animal proteins subject to minor modification to address sustainability issues. The impact of ultrasound application on the yield, techno-functional properties, and molecular characteristics of protein extracted from Moringa oleifera seeds was studied. For this purpose, a central composite design (CCD) was applied to optimize ultrasound-assisted extraction (UAE) parameters such as amplitude (25–75%), solute-to-solvent ratio (1:10–1:30), and pH (9–13) for obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Phenolic content, including condensed tannins, anthocyanins, and gallotannins, is determined in extracts that are associated with biological activities. Flavonoids are extracted by traditional extraction methods, while rutin is predominantly extracted using unconventional methods ( Brighente et al, 2007 ; Fatima et al, 2023 ). The previously mentioned bioactive molecules can be separated in different ways ( Table 1 ), i.e., via conventional methods (maceration, solvent extraction, soxhlet extraction, and vapor or hydrodistillation) ( Waliat et al, 2023 ) and innovative technologies (emulsion liquid membrane, ultrasound-assisted extraction, enzyme-associated extraction, pulsed electric field, microwave-assisted extraction, and supercritical fluid) ( Aadil et al, 2015 ; Maqbool et al, 2022 ; Arshad et al, 2023 ).…”
Section: Different Extraction Methods Of Active Compounds From Summer...mentioning
confidence: 99%
“…Phenolic content, including condensed tannins, anthocyanins, and gallotannins, is determined in extracts that are associated with biological activities. Flavonoids are extracted by traditional extraction methods, while rutin is predominantly extracted using unconventional methods ( Brighente et al, 2007 ; Fatima et al, 2023 ). The previously mentioned bioactive molecules can be separated in different ways ( Table 1 ), i.e., via conventional methods (maceration, solvent extraction, soxhlet extraction, and vapor or hydrodistillation) ( Waliat et al, 2023 ) and innovative technologies (emulsion liquid membrane, ultrasound-assisted extraction, enzyme-associated extraction, pulsed electric field, microwave-assisted extraction, and supercritical fluid) ( Aadil et al, 2015 ; Maqbool et al, 2022 ; Arshad et al, 2023 ).…”
Section: Different Extraction Methods Of Active Compounds From Summer...mentioning
confidence: 99%
“…As this study found and many studies have also reported, an increasing trend is seen in the yield of protein with the increase in the time of passing the sonication waves into the medium 36−38 as a consequence of cavitational phenomena, a mechanical force that aids in the migration of protein molecules through the cell membrane by disrupting the cell membrane. 36,39 Finally, the highest yield of protein was found at 200 W for 20 min (Table 1). A slight drop was seen as the time increased further.…”
Section: Determining the Effect Of Us On Protein Yieldmentioning
confidence: 96%
“…Peanut (Arachis hypogae L.), as one of the most important oil crops in the world, is rich in oil and protein, with high nutritional value and flavour (Boukid, 2022). The high nutritional value of peanuts is attributed to the high oil and protein contents, and the relatively higher levels of bioactive compounds (such as tocopherols, flavonoids, phytosterols, and resveratrol), and easier to digest than animal proteins (Fatima et al, 2023;Suleman et al, 2023;Khalid et al, 2023b).…”
Section: Introductionmentioning
confidence: 99%